Once Again on the Translation of the Manchu Version of “Yuanshi” » - S.V. Sidorovich (Золотоордынское обозрение, 2015)
The author of the article continues the study of Russian translation of the monument “Dai Yuan gurun-i suduri” – Manchu variant of the “Yuanshi” (The History of the Yuan [dynasty]) chronicle. The two most typical examples of erroneous interpretation were cited from the recently published translation of the fourth scroll of the monument and then analyzed. Also the author’s own variant of the translation is offered. Thinking over the causes of the errors in translation of the particular parts of the monument, the author points at the necessity of comparison of the Manchu version with the primary source written in Chinese and appealing to more additional information, i.e. sources and researches.